Profitability and risk in relation to credit monitoring and recovery strategies of Palestinian commercial banking system - Alaeddin, Omar; Thabet, Wael M.; Thabet, Ahmed A. S.; Nurmukhamedov, Bakhodir (Gyandhara International Academic Publications, 2019)
Purpose of Study: This study implemented an empirical investigation for the relationship between credit risk management and profitability of commercial banks in Palestine over the period of 3years (2015-2018), ten commercial banks were selected. Methodology: The financial theory was employed to create the research model; Return on Asset (ROA) is defined as proxies of profitability while credit monitoring (LLPI) is defined as proxies of credit risk management. Panel model analysis was used to estimate the determination of the profit function. Results: Statistical results revealed that the relationship between the credit monitoring and commercial banks profitability is negative significant (β= -3.419, P ˂ 0.05). Therefore, the results improve that LLPI has a significant effect on Palestinian commercial banks profitability's.